2016
DOI: 10.1371/journal.pone.0163132
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Higher Reported Pain Levels in Patients with Chronic Musculoskeletal Pain: A Cross-Sectional, Correlational Analysis

Abstract: BackgroundChronic musculoskeletal pain is highly prevalent, disabling, and costly, and has many negative effects on quality of life. The aim of this study was to investigate factors associated with higher reported pain levels in patients with chronic musculoskeletal pain among demographic, clinical, and psychological factors, and to evaluate whether insomnia is independently associated with pain intensity in this population.MethodsA total of 357 patients with chronic musculoskeletal pain (pain duration ≥ six m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
2
15
0
1
Order By: Relevance
“…Sleep disturbance is frequently reported by patients afflicted by chronic pain, but it is often seen as a secondary symptom rather than an independent symptom. Because pain mediates sleep problems, adequate pain management is thought to lead to improved sleep in patients with chronic pain (Park, Yoon, Yoon, Moon, & Kim, ; Power, Perruccio, & Badley, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbance is frequently reported by patients afflicted by chronic pain, but it is often seen as a secondary symptom rather than an independent symptom. Because pain mediates sleep problems, adequate pain management is thought to lead to improved sleep in patients with chronic pain (Park, Yoon, Yoon, Moon, & Kim, ; Power, Perruccio, & Badley, ).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps unsurprisingly, our study data identified a relationship between greater pain catastrophizing and higher severity of ankle pain. This is consistent with previous research that reported a relationship between pain catastrophizing and pain intensity 415,425,426,427 , but not self-reported function 428 . Thus, pain catastrophizing should be assessed in individuals with chronic ankle symptoms, particularly those with high pain severity.…”
Section: Discussionsupporting
confidence: 92%
“…The recognized structure–symptom discordance in knee osteoarthritis (OA) points to the importance of factors other than structural joint pathology in explaining the differences in pain experienced by people with knee OA and, by extension, the susceptibility to developing knee pain in OA . It is possible that, independent of structural pathology, multiple characteristics such as psychological factors, sleep, and nervous system sensitization may increase the risk of an individual developing symptoms . Pain in knee OA has intermittent and constant components, with the former defining the early stages of the disease in which pain, often absent for periods of time, is triggered by activities with high force or loads .…”
Section: Introductionmentioning
confidence: 99%